Histological staining of tick bite skin biopsies for spirochetes and Powassan virus RNA - Jihane Oufattole; Anne Piantadosi; Sam R. Telford; Alvaro C. Laga; Isaac H. Solomon (Microbiology Spectrum, 2025)
ABSTRACT Ixodes scapularis is a vector of several human pathogens in the United States, including Borrelia burgdorferi, the cause of Lyme disease, and Powassan virus (POWV), an emerging cause of severe encephalitis. Skin biopsies from tick bite sites are frequently collected and tested for the presence of spirochetes (Borrelia spp.), which remain elusive. POWV testing is not performed despite the increasing incidence of POWV encephalitis. To determine the utility of staining skin biopsies for tick-borne pathogens, formalin-fixed paraffin-embedded specimens from 2010 to 2023 were examined by hematoxylin and eosin, Warthin–Starry stain, spirochete immunohistochemistry, and POWV in situ hybridization (ISH). These assays were optimized by staining histological sections from whole ticks, from which spirochetes were detected in two out of 14 patient-derived specimens, and POWV RNA was detected in multiple experimentally infected ticks. None of the 36 skin biopsies were positive for spirochetes, including 20 with retained tick mouth parts and six from patients with positive Lyme serology. POWV ISH was negative in all biopsies, including one laboratory confirmed case. Combining patients with skin biopsies and whole ticks (n = 50), spirochetes were detected in specimens from only 1/5 (20%) patients with suspected erythema chronicum migrans (ECM). Although limited, our data suggest a poor correlation between ECM and the detection of spirochetes, findings in concordance with the published literature. Similarly, the absence of detectable POWV RNA in any of the tested skin biopsies or patient-derived ticks, including one laboratory confirmed case, suggest the limited utility of POWV ISH for clinical use without further analysis with a larger sample size.IMPORTANCETick-borne infections, including Lyme and Powassan encephalitis, cause significant morbidity and mortality and are challenging to diagnose and study in humans. We examined skin biopsies from patients with tick bites to look for direct evidence of microbes by histochemical, immunohistochemical, and in situ hybridization stains. To validate these assays, we also tested the same stains on histological sections from whole ticks infected with spirochetes or Powassan virus. Examination of skin biopsies using similar tools may prove valuable in studying the pathogenesis of diseases, such as southern tick-associated rash illness, for which a causative pathogen has not yet been identified.